Tres postales caballerescas para un viaje literario (con un epílogo poético) - Lucía Megías, José Manuel (Revista de Filología Románica, 2006)
Starting from the descriptions of cities in the handwritten chivalric books, Flor de caballerías and Crónica de Adramón, and explaining how the Spanish language is described in some Italian cities, in the Lozana andaluza by Francisco Delicado, this work proposes three visions of the city in the Siglos de Oro literature, which is complementary to the ideal place for the knight, in the Third Letter by Eminescu.